2021
DOI: 10.1021/acs.jnatprod.1c00677
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrolucilactaene, a Potent Antimalarial Compound from Fusarium sp. RK97-94

Abstract: A recently discovered secondary metabolism regulator, NPD938, was used to alter the secondary metabolite profile in Fusarium sp. RK97-94. Three lucilactaene analogues were detected via UPLC-ESI-MS analysis in NPD938-treated culture. The three metabolites were successfully purified and identified as dihydroNG391 (1), dihydrolucilactaene (2), and 13α-hydroxylucilactaene (3) via extensive spectroscopic analyses. DihydroNG391 (1) exhibited weak in vitro antimalarial activity (IC 50 = 62 μM). In contrast, dihydrolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Other effective chemical epigenetic modifiers screened for a fungal secondary metabolism included histone acetyltransferase modifiers (i.e., anacardic acid) [ 31 ], histone methyltransferase modifiers (i.e., BRD4770) [ 32 ], proteasome modifiers (i.e., bortezomib) [ 33 , 144 ], and modifiers with unclear mechanisms (i.e., NPD938) [ 34 , 49 ].…”
Section: Effects Of Other Chemical Epigenetic Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Other effective chemical epigenetic modifiers screened for a fungal secondary metabolism included histone acetyltransferase modifiers (i.e., anacardic acid) [ 31 ], histone methyltransferase modifiers (i.e., BRD4770) [ 32 ], proteasome modifiers (i.e., bortezomib) [ 33 , 144 ], and modifiers with unclear mechanisms (i.e., NPD938) [ 34 , 49 ].…”
Section: Effects Of Other Chemical Epigenetic Modifiersmentioning
confidence: 99%
“…In addition, the opening of the tetrahydrofuran ring of 13α-hydroxylucilactaene ( 478 ) to form dihydrolucilactaene ( 477 ) resulted in a 100-fold increase of activity, confirming that the tetrahydrofuran ring was not more important for activity than the intact pyrrolidone ring and removal of epoxide. Furthermore, dihydrolucilactaene ( 477 ) exhibited weak cytotoxic activity against HeLa and HL-60 cells with IC 50 values of 21 μM and 37 μM, respectively [ 49 ].…”
Section: Effects Of Other Chemical Epigenetic Modifiersmentioning
confidence: 99%
“…The IC 50 value of inhibition of cellular protein degradation by 7 was calculated from the degradation rate 24 and found to be 7.7 μM. Various biological activities of 7 and 8 have been reported to date, such as cell cycle inhibitory activ- ity, 37 alkaline phosphatase inhibitory activity, 39 and antimalarial activity, 40 but this is the rst report of their UPS inhibitory activities.…”
Section: Ng391 (7) and Lucilactaene (8)mentioning
confidence: 99%
“…Despite the great potential of microorganisms to produce new secondary metabolites of high therapeutic value, large-scale genome sequencing and bioinformatics studies have revealed that many biosynthetic gene clusters (BGCs) remain silent under typical laboratory conditions. This limits the effectiveness of conventional isolation methods for discovering novel natural products. To address this challenge, several approaches were developed to activate silent BGCs. , Culturing one microbial strain in various culture conditions including media composition, aeration, culture vessel, or addition of enzyme inhibitors can nonselectively activate silent BGCs; thus more cryptic metabolites could be accessible. , Chemical elicitation of microbial cultures, coculture, ribosome engineering, manipulation of global regulators, , heterologous expression, , promoter exchange, , gene knockout, and gene cluster refactoring are also used to activate silent BGCs in microorganisms. The expression of cluster-specific regulators also represents a promising approach toward the selective activation of silent BGC and the production of novel natural products …”
mentioning
confidence: 99%